Working time developments in the 21st century : work duration and its regulation in the EU - Cabrita, Jorge; Boehmer, Simon; Galli da Bino, Camilla; European Foundation for the Improvement of Living and Working Conditions (Publications Office of the European Union, 2016)
Summary.
Keywords: työaika : EU-maat; työaika : EU-oikeus